Dimensionamento dos profissionais de enfermagem de uma clínica cirúrgica de um hospital de ensino - Rorato, Alexsandra Micheline Real Saul (2016)
Descriptive study of quantitative nature, which aimed to evaluate the quantitative and qualitative of the nursing staff of the Surgical Clinic of a teaching hospital in southern Brazil, composed of 52 beds. 465 patients participated in the study; the ethical precepts of Resolution 466/2012 were followed, under CAAE No. 52487116.6.0000.5346. Data were collected from April 12 to July 10, 2016, according to the methodological guidelines proposed by Gaidzinski (1998). To classify the patients, the instrument of Fugulin et al (2006) was used. For the hours of assistance and percentage distribution of each category, the standards of the COFEN Resolutions No. 293/2004 and 0527/2016 were followed. Inpatients were evaluated daily, with 4164 evaluations performed. Patients were classified in five levels of care dependency, being the majority, 35% (1442), with care profile corresponding to the intermediate care category; 30% (1263), with high dependency care; 21% (873) were classified with minimal care; 8% (331) with semi-intensive care and 6% (255) with intensive care. The technical safety index determined by the study for nurses was 40.50% and 37.83% for nursing technicians, being that among the absences foreseen by weekly rest days was 17%. Of the unforeseen absences, 6.65% were by nurses and 4.53% by assistants and technicians, being the majority due to medical licenses. The current frame of the nursing service is 16 nurses and 45 nursing technicians and assistants, during the period of data collection. According to the COFEN Resolution of 2004, the project is 27 nurses and 55 technicians and assistants, while in the Resolution of 2016 the project was 29 nurses and 57 technicians and nursing assistants. The proportion of the nursing staff is below what is recommended by the Resolutions, which may compromise the quality of care and patient safety, causing sickness in the nursing team and increasing absenteeism. This study made possible the dimensioning of the nursing team, which is part of the managerial action of the nurse, collaborates to achieve care, teaching and research in the surgical clinic, thus pointing out the necessary conditions for improving the quality of care with patient safety and team productivity.